2020
DOI: 10.26452/ijrps.v11ispl3.2963
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of Mandibular Third Molar Pericoronitis Among Smokers And Evaluation Of Its Treatment Outcomes - A Retrospective Study

Abstract: Pericoronitis is an infectious disease affecting the operculum overlying a semi-erupted or erupting tooth. Pericoronitis occurs mainly or particularly on the lower third molars. It is painfully debilitating at times and it's a common periodontal emergency found for many diseases, with tobacco being the major modifiable risk factor. It has a negative impact over oral health and oral hygiene. The aim of this study is to analyse the prevalence of pericoronitis among smokers. Patients included in this retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…If pericoronitis manifests as an accompaniment to another disease, it can be classified as sequela to a compromised immune system, ergo as an opportunistic-like infection. Additional findings indicated an increased prevalence of pericoronitis in smokers [ 34 ]. Some studies suggested competitive sports activities are a risk factor for pericoronitis as its incidence in sport professionals was reported to be between 5–39% [ 35 , 36 , 37 ].…”
Section: Part A: Pericoronitis Evidence-based Therapymentioning
confidence: 99%
“…If pericoronitis manifests as an accompaniment to another disease, it can be classified as sequela to a compromised immune system, ergo as an opportunistic-like infection. Additional findings indicated an increased prevalence of pericoronitis in smokers [ 34 ]. Some studies suggested competitive sports activities are a risk factor for pericoronitis as its incidence in sport professionals was reported to be between 5–39% [ 35 , 36 , 37 ].…”
Section: Part A: Pericoronitis Evidence-based Therapymentioning
confidence: 99%